Genetic Association in Myocardial Infarction: Ethnicity; ABO, Rh, Le(a), Xg(a) Blood Groups; G6PD Deficiency; and Abnormal Haemoglobins - Saha, N. (1973)
Four hundred and eighty-six patients with myocardial infarction of both sexes comprising 213 Chinese, 53 Malays, 199 Indians, and 21 Europeans, resident in Singapore were investigated for differences in relative incidence, and for the ABO, Rh, Le(a), and Xg(a) blood groups, G6PD deficiency, and haemoglobin types. Relative incidence of myocardial infarction was appreciably higher among Indians than Chinese and Malays in all age groups, more so in younger people. There was no significant difference in the distribution of the genetic markers between patient and control series in either Chinese, Malays, or Indians.